Perceptual Reorganization of Lexical Tones: Effects of Age and Experimental Procedure - Götz, Antonia; Yeung, H. Henny; Krasotkina, Anna; Schwarzer, Gudrun; Höhle, Barbara (Frontiers in Psychology, 2018)
Findings on the perceptual reorganization of lexical tones are mixed. Some studies report good tone discrimination abilities for all tested age groups, others report decreased or enhanced discrimination with increasing age, and still others report U-shaped developmental curves. Since prior studies have used a wide range of contrasts and experimental procedures, it is unclear how specific task requirements interact with discrimination abilities at different ages. In the present work, we tested German and Cantonese adults on their discrimination of Cantonese lexical tones, as well as German-learning infants between 6 and 18 months of age on their discrimination of two specific Cantonese tones using two different types of experimental procedures. The adult experiment showed that German native speakers can discriminate between lexical tones, but native Cantonese speakers show significantly better performance. The results from German-learning infants suggest that 6- and 18-month-olds discriminate tones, while 9-month-olds do not, supporting a U-shaped developmental curve. Furthermore, our results revealed an effect of methodology, with good discrimination performance at 6 months after habituation but not after familiarization. These results support three main conclusions. First, habituation can be a more sensitive procedure for measuring infants’ discrimination than familiarization. Second, the previous finding of a U-shaped curve in the discrimination of lexical tones is further supported. Third, discrimination abilities at 18 months appear to reflect mature perceptual sensitivity to lexical tones, since German adults also discriminated the lexical tones with high accuracy.